1993
DOI: 10.1113/jphysiol.1993.sp019667
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular sodium activity and its regulation in guinea‐pig atrial myocardium.

Abstract: SUMMARY1. Intracellular Na' activity (aIa) and membrane resting potential were studied in quiescent guinea-pig atrial and papillary muscles by means of Na'-sensitive and conventional microelectrodes. The effects of the cardioactive steroid dihydroouabain (DH11) on aia, force of contraction and sarcolemmal Na', K+-ATPase activity were also investigated.2. In thirty atria and twenty-two papillary muscles, a'a amounted to 8-0 + 0 2 and 4 7 +0 3 mm, respectively (means±+S.E.M.). When both tissues were from the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…While the mechanism of differential Differential Na¤-K¤-ATPase expression J. Physiol. 502.2 pump regulation in the heart appears to be associated with an enhanced protein synthesis (Wang et al 1993), our data showed that in MGB neurones the cell size and the membrane pump density is an important factor. This is supported by the fact that despite the difference in membrane pump signals, the cytoplasmic pools of pump signals in the two cell populations are comparable.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…While the mechanism of differential Differential Na¤-K¤-ATPase expression J. Physiol. 502.2 pump regulation in the heart appears to be associated with an enhanced protein synthesis (Wang et al 1993), our data showed that in MGB neurones the cell size and the membrane pump density is an important factor. This is supported by the fact that despite the difference in membrane pump signals, the cytoplasmic pools of pump signals in the two cell populations are comparable.…”
Section: Discussionmentioning
confidence: 74%
“…If it can be assumed that both ventral and dorsal cell types express primarily the á3 isoform and that they have identical pump stoichiometry and turnover rate, then the density of pump molecules apparently becomes an important factor affecting the amplitude of the pump current. The membrane density of the Na¤-K¤-ATPase varies widely among different cell types and even in a given cell the membrane distribution of pump molecules can be highly heterogenous (Allen et al 1989;Cramb et al 1989;McGrail et al 1991;Ikenouchi, Zhao, McMillan, Hammond & Barry, 1993;Wang et al 1993). An example of such functional differential distribution has been described recently in guinea-pig heart where the atrial and ventricular myocytes are reported to contain different amounts of pump molecules and, as a result, exhibited different contractile force in response to ouabain (Wang et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrogenic activity of the Na¤-K¤-ATPase may play an important role in setting the mode of synaptic transmission in sensory thalamus. (Wang, Schmied, Ebner & Korth, 1993). The lack of a clear pump electrogenic effect in these examples is, however, partly due to the large cell volume and their low input resistance (Thomas, 1972;Lauger, 1991).…”
mentioning
confidence: 99%